2013
DOI: 10.7127/rbai.v7n100098
|View full text |Cite
|
Sign up to set email alerts
|

Produção de melão amarelo sob diferentes densidades de plantio

Abstract: O experimento foi realizado em Aracati-CE, com irrigação localizada por gotejamento. O objetivo do trabalho foi avaliar os efeitos da densidade de plantio (10; 12,5; 16,6 e 25 mil plantas ha -1 ) sobre o rendimento de frutos do meloeiro amarelo, híbrido TP1109. As densidades foram obtidas mantendo-se constante o espaçamento entre fileiras (2,0 m) e variando-se o espaçamento entre plantas (0,50; 0,40; 0,30 e 0,20 m). Foram avaliados o peso por fruto (kg/fruto), número de frutos por planta, produção comercial (k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
4
0
3
Order By: Relevance
“…Similar results with cucurbits confirm the effect of spacing on the number of fruits plant -1 . In pumpkin, Resende et al (2013) found that, at the spacing of 1.0 m between plants, the number of fruits was 38% lower than that observed at spacing of 3.0 m. In yellow melon, the spacing of 0.50 m between plants favored higher fruit production (3.07 fruits plant -1 ) compared to the spacing of 0.20 m (1.43 fruits plant -1 ) (Dantas et al, 2013). In zucchini, the increase in density from 2 to 3 plants m -2 reduced the number of fruits by 52% (Bahlgerdi et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results with cucurbits confirm the effect of spacing on the number of fruits plant -1 . In pumpkin, Resende et al (2013) found that, at the spacing of 1.0 m between plants, the number of fruits was 38% lower than that observed at spacing of 3.0 m. In yellow melon, the spacing of 0.50 m between plants favored higher fruit production (3.07 fruits plant -1 ) compared to the spacing of 0.20 m (1.43 fruits plant -1 ) (Dantas et al, 2013). In zucchini, the increase in density from 2 to 3 plants m -2 reduced the number of fruits by 52% (Bahlgerdi et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Tipos estes que já foram os mais indicados para o mercado interno (Faria et al, 2000). No entanto, atualmente os melões tipo 6 e 7 tem igual preferência pelos mercados interno e externo (Dantas et al, 2013). A fonte de adubo nitrogenado adotado nesta pesquisa foi a ureia e isto pode ter sido uma das causas dos frutos terem apresentado comprimento e diâmetro maiores que os registrados na literatura; Rodrigues et al (2019) constataram aumento de até 175% na biometria de frutos de melão Cantaloupe quando usada a ureia como fonte de nitrogênio para a planta.…”
Section: °Ciclo 2°ciclounclassified
“…It has a high socioeconomic importance for the Northeast region of Brazil, concentrating 95% of the national production. The Pele de sapo melon, is the second most produced melon variety in the region due to its large fruits, good pulp firmness, and greenish color (Figueirêdo et al, 2017;Dantas et al, 2013).…”
Section: Introductionmentioning
confidence: 99%